“Stop Postponing Your Life Until You Lose Weight and Start Living Now”: Vancouver’s Large as Life Action Group, 1979–1985 - Ellison, Jenny (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2007)
AbstractVancouver fat acceptance group Large as Life (LAL) was active between 1979 and 1985. The founding members of LAL met at a Gestalt therapy workshop for fat women only in 1979, but ultimately decided that talking was not enough to resolve the problems they experienced on a day-to-day basis. For these women, fat was not just a feeling but a material problem that could be solved through the development of social sites and services that catered to fat women. These would include fitness classes, fashion shows, clothing swaps and personal development workshops. Using interviews with former Large as Life members, together with articles from the group’s newsletter, The Bolster, this paper examines fat women’s perspectives on femininity, health, and fashion in the 1980s. It argues that the shared practices developed among members of Large as Life are an example of the lived complexity of femininity in the 1980s, and, specifically, offers insight into how women experienced and situated themselves in relation to the beauty and bodily norms of the 1980s.